Direct anonymous authentication scheme for wireless networks under trusted computing - YANG Li1; MA Jian-feng 1; PEI Qing-qi2; MA Zhuo 1 (Tongxin xuebao)
Based on direct anonymous attestation of trusted computing,a wireless anonymous authentication scheme was proposed,the platform of the mobile node was verified by the foreign network agent and the identity of the mobile node user was authenticated by the home network agent and the foreign network agent together.By using of temporary identi-ties and one time secret keys,identity anonymity and domain separation property are achieved.The analysis shows that the scheme is secure,reliable,and with higher performance.